Infección de vías urinarias por enterobacterias betalactamasas de espectro extendido y sus factores asociados en el Hospital Manuel Ygnacio Monteros - Abendaño Legarda, Valentina Giovanna (2021)
Urinary tract infection (UTI) is considered a frequent pathology that generates high costs in medical care every year and therefore represents a major public health problem. The most frequent etiological agents are enterobacteria, which are microorganisms that are part of the gut microbiota. In the recent years, the mechanisms of antibiotic resistance by these bacteria have increased; one of the most common is the production of extended spectrum beta-lactamases (ESBL), which are enzymes that inactivate antibiotics such as penicillins, cephalosporins and monobactams, which decreases therapeutic alternatives for patients. The following research aims to determine the incidence of urinary tract infection by ESBL-producing enterobacteria and its associated factors. The type of study carried out was a descriptive, correlational and cross-sectional level with a retrospective vision, in which 331 patients diagnosed with UTI were included. The study found out that 145 patients (43, 80%) had ESBL enterobacteria UTI and 186 (56.20%) UTI by non-ESBL bacteria. A statistically significant association was established between the developments of urinary tract infection due to ESBL-producing enterobacteria and the following factors: history of urinary tract infection, use of antibiotics in the last three months, hospitalization in the last three months for a period ≥48hours, and use of urinary catheter in hospitalization, with a higher incidence in the age group of 61 years and over and in females. Key words: extended spectrum beta-lactamases, resistance, antibiotics, urinary tract.